PELATIHAN DAN PENDAMPINGAN APLIKASI PAYET PADA PRODUK KULIT KAYU NYAMU DAN ROTAN DI KELOMPOK PERAJIN - Nursiah, Nursiah Nursiah; Tanduh, Yusintha Tanduh; Rahmawati, Reni Rahmawati; Yamani, Zaki Yamani (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2020)
Abstract: Nyamu and Rattan bark by the people of Central Kalimantan in general are only used for binding, making traditional clothes that are used in certain events only. Even though there are still many things that can be made from this Nyamu leather raw material, such as alternative materials for making longsongan bags, modified into bags or wallets which can then be further developed in terms of design. To increase the value of beauty and increase the value of handicraft products made from Nyamu bark such as bags and wallets, it is carried out by means of unified matching sequins as a way to enhance the appearance of the products produced and become a special feature of this Nyamu bark product. PKW which is motivated by the assistance of partners in empowering the community in this activity will provide Training and Assistance in the Black and White Craftsmen Group. The method used is active participatory community empowerment through collaboration with partners namely the transfer of knowledge and technology through training activities. All PKW activities went smoothly according to plan. The partner is able to practice what is involved in the activity and has already produced a bag and wallet product with modified sequins. Based on the results of monitoring and evaluation, around 70% of participants succeeded in sewing wallets and purses, while 90% of participants had already started to be skilled at making various patterns of sequin paintings, and several products were sold. .Keywords: Nyamu bark, rattan, sequin, craftsman.